Changes in postural risk and general health associated with a participatory ergonomics education program used by heavy video display terminal users: a pilot study. - Street SL; Kramer JF; Harburn KL; Hansen R; MacDermid JC (Journal of Hand Therapy)
To determine if a brief, participatory ergonomics education program was associated with changes in work posture and general health of heavy video display terminal (VDT) users, 23 full-time VDT users participated in an on-site, small-group, 60-minute ergonomics education session and 1 week later an individual 15-minute follow-up session at their workstation. Posture was assessed by a blinded tester who scored videotape records to complete the Postural and Repetitiveness Risk Factors Index (PRRI), and general health status was assessed via self-administered Short-Form 36 Health Survey (SF-36) questionnaire before the intervention and again 5 weeks later. Five weeks after the 60-minute session, PRRI scores were 19% lower than were preintervention scores (p < 0.01), indicating lower postural risk. SF-36 physical (2% higher) and mental (4% higher) component scores were not statistically different, however, before and after intervention (p > 0.05). Although the participatory ergonomics education program was associated with improved work posture (PRRI scores) after 5 weeks, general physical and mental health (SF-36 scores) did not change within this time period. These results suggest that a participatory ergonomics program, which is of short duration and minimally disruptive to the normal workplace routine, may have a rapid effect on improving work posture. Although awkward posture is thought to be a risk factor for work-related musculoskeletal disorders, multigroup and long-term randomized trials are required to establish the effectiveness of participatory ergonomics programs in reducing the incidence and severity of musculoskeletal disorders associated with heavy VDT use.